Adhesive bond strength enhancing between carbon fiber reinforced polymer and aluminum substrates with different surface morphologies created by three sulfuric acid solutions. (July 2021) - Cheng, Fei; Hu, Yunsen; Zhang, Xiaoguang; Hu, Xiaozhi; Huang, Zhaohui
Abstract: Optimized porous aluminum (Al) substrates chemically etched by three electrolytes have been prepared in this study. They are used to place multi-walled carbon nanotubes (CNTs) via resin pre-coating (RPC) technique for stronger adhesive bonding with carbon fiber reinforced polymers (CFRP). Shallower channels (~1–2 μm) were etched by 20 wt% H2 SO4 solution, deeper channels (~5 μm) were etched by 20 wt% H2 SO4  + 0.5 wt% C2 H2 O4 (or + 0.5 wt% FeSO4 ) solution. The former has less sub-surface void defect by directly adhesive bonding, its bonded composite has higher shear strength. Through RPC, the latter promotes effective interface behaviors including increasing contact area, reducing void defect and improving mechanical occlusion. Moreover, they have sufficient pore volumes to embed and form quasi-Z-directional CNTs, leading to around 135% improvements in shear strength. Therefore, Al substrate surface with deeper channels potentially contributes to improving adhesive interface and positioning vertical CNTs via RPC to further reinforce adhesive joint.